Relationship between physical activity and the sense of coherence in healthy adults - Miguel Jose Soares-Santeugini; Indira Enith Rodriguez-Prieto; Margareth Lorena Alfonso-Mora; Carolina Sandoval-Cuellar (Atención Primaria)
Objective: This study seeks to stablish a relation between the level of physical activity and the sense of coherence in young adults. Design: Cross sectional and analytical study in healthy young participants. Site: Web form application. Participants: 191 active or inactive adult men or women between the ages of 18 and 45 without cognitive alterations. Professional or amateur athletes were excluded. Main measurements: Correlation between the sense of coherence instrument (SOC-13) and Inventory of Physical Activity Questionnaire (IPAQ) were applied. Results: The physical activity levels in the sample were distributed as: high level 34%, medium level 52%, and low level 13%. The mean of SOC-13 was 52.4. No difference was found when comparing between SOC-13 for each group of physical activity (high: 55, medium: 54, low: 58, p > 0.05), no correlation between SOC-13, age, and MET's reported by participants was found. Conclusions: In healthy individuals, the IPAQ measure of physical activity levels showed no correlation with the sense of coherence in healthy young adults. Apparently, a sedentary lifestyle does not correlate with an individual's self-directed pursuit of health. It is possible that being physically active or sedentary is related to extrinsic variables associated with culture or family environment. Resumen: Objetivo: Este estudio busca establecer una relación entre el nivel de actividad física y el sentido de coherencia en adultos jóvenes. Diseño: Estudio transversal y analítico en participantes jóvenes sanos. Emplazamiento: Aplicación de formulario web. Participantes: Ciento noventa y un hombres o mujeres adultos activos o inactivos de entre 18 y 45 años sin alteraciones cognitivas. Se excluyó a los deportistas profesionales o aficionados. Mediciones principales: Se aplicó la correlación entre el instrumento sentido de coherencia (SOC-13) y el cuestionario de Inventario de Actividad Física (IPAQ). Resultados: Los niveles de actividad física de la muestra se distribuyeron en: nivel alto 34% nivel medio 52% y nivel bajo 13%. La media del SOC-13 fue de 52,4. No se encontraron diferencias al comparar el SOC-13 para cada grupo de actividad física (alto: 55, medio: 54, bajo: 58 p > 0,05), no se encontró correlación entre el SOC-13, la edad y los MET reportados por los participantes. Conclusiones: En individuos sanos, la medida IPAQ de los niveles de actividad física no mostró correlación con el sentido de coherencia en adultos jóvenes sanos. Aparentemente, un estilo de vida sedentario no se correlaciona con la búsqueda autodirigida de la salud por parte del individuo. Es posible que ser físicamente activo o sedentario esté relacionado con variables extrínsecas asociadas a la cultura o al entorno familiar.